Lone star law - Randisi, Robert J. (Pocket Books, 2020)
A collection of twelve tales of the Old West chronicles the exploits of the legendary Texas Rangers, in an anthology featuring such authors as Louis L'Amour, Elmer Kelton, and Ed Gorman.